Multilayer nanoparticles for sustained delivery of exenatide to treat type 2 diabetes mellitus - Kim, Jae Yeon; Lee, Hwanbum; Oh, Keun Sang; Kweon, Seho; Jeon, Ok-cheol; Byun, Youngro; Kim, Kwangmeyung; Kwon, Ick Chan; Kim, Sang Yoon; Yuk, Soon Hong (ELSEVIER SCI LTD, 2013)
A method for the sustained delivery of exenatide was proposed using nanoparticles (NPs) with a core/shell structure. The interactions between lipid bilayers and Pluronics were utilized to form various NPs using a layer-by-layer approach. Transmittance electron microscopy and dynamic light scattering were used to examine the morphology of the NPs. The in vitro release pattern was observed as a function of changes in the structure of the NPs, and the structural integrity of exenatide released was examined by SDS-PAGE analysis. Pharmacokinetics and antidiabetic effects were also observed with the structural change of NPs using in vivo animal models. In vitro-in vivo correlation was discussed in relation to manipulation of the NP structures. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: DRUG-DELIVERY; CORE/SHELL NANOPARTICLES; LIPOSOME FUSION; VESICLE FUSION; EXENDIN-4; CAPSULES; BILAYER; RECEPTOR; CORE